RAPID MAXILLARY EXPANSION (SARMS) SURGICALLY ASSISTED IN ADULT PATIENTS - Cristian Constantin Budacu; Aurel Nechita; Doriana Agop Forna; Norina Consuela Forna; Gabriela Stan; Kamel Earar; Trifautanu Petru; Magdalena Miulescu (Romanian Journal of Oral Rehabilitation, 2024)
Surgically assisted rapid maxillary expansion (SARMS) is an innovative procedure in orthodontics aimed at treating jaw discrepancies and correcting tooth and jaw alignment problems in adult patients. This technique involves the use of an expansion device which, when surgically assisted, can provide significant benefits in terms of accelerating the expansion process. The SARM procedure meets the needs of adult patients, who often experience increased jaw bone and difficulty achieving the desired expansion through traditional methods. Assisted surgery is often necessary to unlock bones and allow controlled and effective expansion. The benefits of the surgically assisted SARMS procedure in adult patients are varied and cover aspects such as efficiency in treating jaw discrepancies, accelerating the expansion process, improving aesthetics, and personalizing treatment. With a carefully planned and executed approach, SARM can be an effective and beneficial solution for patients with complex orthodontic needs. Determining the need for WIREs in the initial assessment is a complex process and depends on a variety of individual factors. An interdisciplinary approach and open communication between the patient and the medical team are essential for making an informed decision.